Respuesta :
If you would like to solve the equation a = 2 + 3a + 10, you can do this using the following steps:
a = 2 + 3a + 10
-2 - 10 = 3a - a
-12 = 2a /2
a = -6
The correct result would be -6.
a = 2 + 3a + 10
-2 - 10 = 3a - a
-12 = 2a /2
a = -6
The correct result would be -6.
Answer:
Option 3rd is correct
a = -6
Step-by-step explanation:
Given the equation:
[tex]a = 2+3a+10[/tex]
Like terms are those terms which have same variable to the same power.
Combine like terms we have;
[tex]a = 12+3a[/tex]
Subtract 3a from both sides we have;
[tex]a-3a = 12+3a-3a[/tex]
Simplify:
[tex]-2a = 12[/tex]
Divide both sides by 2 we have;
[tex]a = -6[/tex]
therefore, the value of a is, -6